PERLINDUNGAN HUKUM TERHADAP PEREMPUAN PENYANDANG DISABILITAS DALAM BIDANG KETENAGAKERJAAN: Legal Protection for Women with Disabilities in The Field of Employment - Anggraeni, Felicia; Retnowulandari, Wahyuni (AMICUS CURIAE, 2025)
The realization of human rights is a fundamental right of every individual, including women with disabilities. The fulfillment and implementation of rights related to women with disabilities must be prioritized. However, existing legislation does not yet provide specific regulations offering greater protection for women with disabilities in the employment sector, despite the necessity of such regulations due to their heightened vulnerability to multiple layers of discrimination. The problem statement of this article is how are the fulfillment and implementation of the rights of women with disabilities in the employment sector regulated by the laws and regulations? The purpose of this article is to describe the fulfillment and implementation of the rights of women with disabilities in the employment sector according to the applicable laws and regulations. This study employs a normative legal research method, utilizing secondary data. It is descriptive-analytical and analayzed qualitively, with conclusions drawn using a deductive approach. The findings show that the rights of women with disabilities in the workplace are not effectively implemented due to a lack of specific regulations and ongoing discrimination. The conclusion is that specific regulations for women with disabilities in the employment sector are urgently needed, given their hightened vulnerabilitu to multiple forms of discrimination.